2017
DOI: 10.1080/09658211.2016.1275699
|View full text |Cite
|
Sign up to set email alerts
|

A narrative synthesis of the applicability of the CaR–FA–X model in child and adolescent populations: a systematic review

Abstract: The CaR-FA-X model [Williams, J. M. G., Barnhofer, T., Crane, C., Hermans, D., Raes, F., Watkins, E., … Dalgleish, T. (2007). Autobiographical memory specificity and emotional disorder. Psychological Bulletin, 133(1), 122-148. doi: 10.1037/0033-2909.133.1.122 ] is the most prominent and comprehensive model of overgeneral autobiographical memory (OGM) and provides a framework for OGM. The model comprises of three mechanisms, capture and rumination, functional avoidance and impaired executive control. These can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 87 publications
(328 reference statements)
0
9
0
Order By: Relevance
“…Perhaps during the preschool years, when trauma has occurred relatively recently given the age of the child, such avoidant approaches may have yet to be fully integrated into the general mnemonic strategies of abused children. It is noteworthy that the children in the current investigation were considerably younger than the child participants included in previous research regarding AMS in trauma-exposed youth (e.g., adolescence; see Hitchcock et al, 2014;Stewart et al, 2017 for reviews) and their maltreatment experiences occurred within one year of the AMS assessment for the majority of the children.…”
Section: Discussionmentioning
confidence: 90%
“…Perhaps during the preschool years, when trauma has occurred relatively recently given the age of the child, such avoidant approaches may have yet to be fully integrated into the general mnemonic strategies of abused children. It is noteworthy that the children in the current investigation were considerably younger than the child participants included in previous research regarding AMS in trauma-exposed youth (e.g., adolescence; see Hitchcock et al, 2014;Stewart et al, 2017 for reviews) and their maltreatment experiences occurred within one year of the AMS assessment for the majority of the children.…”
Section: Discussionmentioning
confidence: 90%
“…This work was synthesized by Williams (2006) and Williams et al (2007) in their seminal Capture and Rumination, Functional Avoidance and eXecutive capacity (CaRFAX) model of rAMS. These three CaRFAX pathways work both independently and in combination to compromise memory specificity (Sumner et al, 2014), though the exact nature of their interaction may differ between age-groups (Stewart, Hunter & Rhodes, 2017). Comprised memory specificity then leads to several consequences that are hypothesised to in turn contribute to the emergence and maintenance of emotional disorders.…”
Section: Social Memorymentioning
confidence: 99%
“…Inhibition was measured via a temperament questionnaire, but for a clearer understanding of the mechanism of impaired executive control studies need to include a behavioral inhibition task (Stewart , Hunter & Rhodes, 2017), and to examine executive control in older adolescents. Additionally, conflicting evidence concerning executive control and OGM has been reported, found no relationship between verbal fluency and OGM and Valentino et al, (2012) reported inhibition (via a colour word inference task) and OGM were not significantly correlated.…”
mentioning
confidence: 99%
“…No research in young people has yet looked at the relationship between OGM and the two rumination sub types separately in young people with depression symptoms. In a recent review of the relationship between exposure to trauma and OGM, (Stewart et al, 2017) reported that no study has yet included all components of the CaR-FA-X model with young people.…”
mentioning
confidence: 99%